Per un'edizione critica della versione toscana dell'«Histoire ancienne jusqu'a Cesar» contenuta nel manoscritto Hamilton 67: «Le verace istorie romane» (Carte Romanze, 2021)
I present in this article a notice that a book will shortly appear in print, entitled Le verace istorie Romane (The True Roman Histories) based on manu- script Hamilton 67 of the German State Library of Berlin, dated 1313. In it, I point out the connection between diffent manuscripts, the writer Lapo Corsini’s form of writing and its history, and its unique contamination between a transla- tion from French, the Histoire ancienne, and its Latin source, Orosius, Histories Against the Pagans. At the end, I present two samples of the text, from the Han- nibal story and the wonders that appear, and the plague and infestation of cric- kets.